Berita Perombakan Atau Reshuffle Menteri Kabinet Kerja JOKOWI-JK (Analisis Framing Berita Reshuffle Kabinet Kerja Jokowi-JK di Media Online Tempo.co edisi 06 Mei - 13 Agustus 2015) - Hasanah, Putri Uswatun; , Drs. Joko Sutarso, S.E, M. Si; , Agus Triyono, S.sos, M. Si (2016)
Abstract The main characteristics of online media is speed in conveying information and events, but it may be a deficiency in the presentation of news. The presentation of news in a number of online media is heavily influenced by the personal perspective of journalists, it is visible from constructing news on online news sites. Because every journalist has a different view in the view of reality. Tempo.co is a news portal which first appeared in Indonesia since 1995. After the procession of presidential elections Tempo.co visitors increased by 62.5 percent. News reshuffle work was news that a lot of attention from the public, especially visitors Tempo.co. The purpose of this study was to determine how to construct Tempo.co news or reshuffle cabinet reshuffle work Jokowi-JK. This study uses qualitative descriptive analysis method of framing a model Zhodang Pan and Gerald M. Kosicki. The results of this study indicate that Tempo.co sought to promote objectivity in presenting the news. Framing built by Tempo.co shows three major issues. First, Jokowi hesitate in taking the decision. Second, the poor performance of both economic sector. Third, Jokowi intervention by political parties. Keywords: Cabinet reshuffle, Framing Analysis, Tempo.co